Evaluation of E-Government Services in Jayawijaya Regency Post Expansion of the Papua Pegunungan Province Using the UTAUT Model - Tabuni, Yohanes (Journal of Social Research, 2023)
In the era of economic, political, and technological globalization, the importance of Good Government and Clean Government encourages the Indonesian Government to implement information and communication technology. The aim is to increase effectiveness, efficiency, transparency, and accountability in public services and government business processes. The e-government concept includes the relationship between government and government (G2G), government and business (G2B), government and ASN (G2E), and government and society (G2C). Websites are a crucial component in e-government, providing information accessibility and increasing openness. This research aims to evaluate the quality of the Jayawijaya Regency Government Website. In this research, a purposive sampling technique was used. This research used 100 samples or respondents. Data analysis in this research was carried out using descriptive analysis methods of averages and percentages. The approach applied is the UTAUT method (Unified Theory of Acceptance and Use of Technology. UTAUT is formed by three main factors, condition of work facilities, impact of information technology systems, and service user request. The variables CWF, IITS, and SUR simultaneously influence the variables EC, and ( 2) the dependent variable UB is simultaneously influenced by the EC variable. The CWF variable partially and significantly influences the EC variable. (2) the IITS variable partially and significantly influences the EC variable (3) the SUR variable partially and significantly influences the EC variable. The independent variable influences EC is 47.1% while the independent variable EC influences UB by 55.3%.